IEcology: Harnessing Large Online Resources to Generate Ecological Insights. (July 2020) - Jarić, Ivan; Correia, Ricardo A.; Brook, Barry W.; Buettel, Jessie C.; Courchamp, Franck; Di Minin, Enrico; Firth, Josh A.; Gaston, Kevin J.; Jepson, Paul; Kalinkat, Gregor; Ladle, Richard; Soriano-Redondo, Andrea; et al.
Abstract : Digital data are accumulating at unprecedented rates. These contain a lot of information about the natural world, some of which can be used to answer key ecological questions. Here, we introduce iEcology (i.e., internet ecology), an emerging research approach that uses diverse online data sources and methods to generate insights about species distribution over space and time, interactions and dynamics of organisms and their environment, and anthropogenic impacts. We review iEcology data sources and methods, and provide examples of potential research applications. We also outline approaches to reduce potential biases and improve reliability and applicability. As technologies and expertise improve, and costs diminish, iEcology will become an increasingly important means to gain novel insights into the natural world. Highlights: iEcology is a new research approach that seeks to quantify patterns and processes in the natural world using data accumulated in digital sources collected for other purposes. iEcology studies have provided new insights into species occurrences, traits, phenology, functional roles, behavior, and abiotic environmental features. iEcology is expanding, and will be able to provide valuable support for ongoing research efforts, as comparatively low-cost research based on freely available data. We expect that iEcology will experience rapid development over coming years and become one of the major research approaches in ecology, enhanced by emerging technologies such as automated content analysis, apps, internet of things, ecoacoustics, web scraping, and open source hardware.